THE MOUNTAIN REPUBLIC IN CONCEPTIONS OF THE BRITISH MISSION AND THE VOLUNTARY ARMY (1919-1920) - K. Ambartsumyan (Гуманитарные и юридические исследования)
The article actualizes the problem of interaction between the British mission, the Volunteer Army and the government of the Mountain Republic in 1919-1920. Using published and archival sources the author reveals discrepancy between the aims of London in the Caucasus, the standpoint stated at the peace conference in Paris, and the policy of the British mission and the leadership of the Volunteer Army in the North Caucasus. For the first time, the North Caucasian region and the Mountain Republic are considered in the context of international relations that reveals different ideas about the future of the region on the part of the British authorities, the leadership of the Volunteer Army, and the representatives of the mountain government. Based on these ideas, a real policy was implemented. The novelty of the study is in the view of the situation in the North Caucasus from geopolitical interests of London, which saw in it the extension of its Middle East policy. If we consider the situation within only the Greater Caucasus, we will notice that greater interest was shown precisely in the South Caucasus; the northern part played an auxiliary role. Common and specific features were identified in the positions of the leadership of the Armed Forces of the Southern Russia and the Russian Political Council. The Russian Political Council viewed the Greater Caucasus as part of a united and integral Russia. Sergei Sazonov, the former imperial foreign minister, saw no chance of success in gaining independence for the Caucasian republics. A. I. Denikin had to act in specific circumstances and at that moment, he could not afford such military activity in the South Caucasus, as in the North Caucasus. For the British mission in Caucasus, the Mountain Republic was not a priority, the issue of its recognition was of little interest to them. The mission was military and they were involved in politics out of necessity, initially such a task was not set.